Improving Student Learning Outcomes by Using the Peer Tutor Method in Mixed Music Ensemble Learning - Sedino, Apris; Handra Kadir , Tulus (Universitas Negeri Padang, 2024)
The purpose of this study was to improve the learning outcomes of students' music ensembles using the peer tutor method in grade XI F 6 SMA Negeri 3 Padang. This study used Classroom Action Research. The research instrument is the researcher himself. Data collection techniques use observation, interviews, documentation and tests. The data is analyzed by a percentage formula. The use of peer teaching methods can improve students' ability to play ensembles at SMA Negeri 3 Padang. The application of peer tutor methods in learning mixed music ensembles in groups can raise students' enthusiasm and performance in learning activities. The results of learning completeness in cycle I were 60.25 with fairly good criteria, in cycle II learning completeness increased which was obtained 86.50 with good criteria. The increase from cycle I to cycle II was 26.25%.